Exploring the Perceptions and Usage of Social Networking Sites among Distance Learning Students in Nigeria - Nnaka, Chibuogwu V. (West African Journal of Open and Flexible Learning, 2016)
Social networking sites have become popular virtual meeting places that allow young adults to interact and socialize with their peers. This study was carried out to investigate the perceptions and usage of social networking sites among distance learning students in Nigeria. The objectives of the study are to identify students’ perception of social media networking, to ascertain the various categories of social networking sites used by distance learning students, to examine the frequency of usage of the social networking sites by the students and to examine their purposes of using social networking sites. A descriptive survey design was adopted for the study. Four hundred students were selected by simple random sampling techniques from students of the National Open University of Nigeria. A structured questionnaire was designed, validated and distributed among the sampled students. Descriptive statistics was used to analyse the data. Findings reveal that social networking sacs are mostly being used by students for purposes such as interacting with friends, and family, discussing national issues rather than for educational purposes. The distance learning students perceive social networking sites as interesting platforms for achieving academic excellence. The students use social media daily. Facebook was the most utilized social networking site. Seduction in time for studying and providing an enabling environment for cybercrimes were the two major negative effects that social networking sites had on students.